QoS-driven power and time allocation scheme for spectrum leasing in overlay cognitive radio networks - Roumeliotis, Anargyros J; Vassaki, Stavroula; Panagopoulos, Athanasios D (IET communications, 2018)
The coexistence of a primary user (PU) with a secondary user (SU) is studied in an overlay cognitive radio network (CRN) which is proposed as an efficient technique to treat with the problem of spectrum underutilisation. A cooperative spectrum leasing process under the decode and forward protocol is considered among the PU and SU. Assuming users' specific Quality of Service requirements, a joint power and time allocation scheme for maximising the PU's cooperative effective capacity subject to minimum SU's and PU's effective capacities and maximum SU's instantaneous power transmission constraints is proposed. Its performance is close to the optimal one, that is computed using the exhaustive search scheme. A two-step solution is applied considering the fundamentals of convex optimisation theory and closed-form power and time expressions are extracted. As simulation results prove, the proposed scheme outperforms a less sophisticated scheme considering power allocation under constant time. Finally, the proposed algorithm is incorporated in a multi-user CRN scenario where efficient matchings among the PUs and the SUs are investigated targeting to the increase of PUs' cooperative performance applying the matching theory.